Geophysical and Geochemical Evidence for a New Mafic Magmatic Province Within the Northwest Shelf of Australia - C. T. G. Yule; C. Spandler (Geochemistry, Geophysics, Geosystems, 2022)
Abstract The formation of mafic magmatic provinces are significant geological events that can drive mass extinctions and continental rifting and can influence basin evolution, petroleum prospectivity and mineralization. Buried magmatic provinces, however, are rarely identified and difficult to define. The Northwest Shelf of Australia contains large volumes of potentially interconnected mafic igneous material across several sedimentary basins. However, limited study and a lack of surface exposure have prevented detailed description and classification of these rocks. In this study, the distribution and composition of these mafic igneous rocks are described using an integrated geophysical and geochemical approach, which included over 10,000 km line length of 2D seismic data, well log data and chemical analysis of samples from 14 wells across the Browse, Roebuck, Canning and North Carnarvon basins. Using this combined data set, we demonstrate interconnectivity of buried mafic igneous rocks across the Northwest Shelf and calculate a total surface area exceeding 280,000 km2 and a cumulative minimum volume of ∼140,000 km3. Petrology and geochemistry of samples indicate they are basaltic and doleritic with alkaline and sub‐alkaline compositions and formed in a continental rift setting. Collectively, the igneous rocks meet the criteria for classification as a mafic magmatic province (MMP) and closely match the criteria required for classification as a large igneous province (LIP). Emplacement of the newly defined Northwest Shelf MMP may represent hotspot magmatism that could have initiated rifting of the Cimmerian Block from NW Australia during the Permian and could have potential for future, large scale CO2 sequestration and storage.